Přirozený vývoj bikuspidální aortální chlopně - Michelena, Hector I (Clinical Cardiology Alert, 2008)
Bicuspid aortic valve is frequent and is reported to cause numerous complications, but the clinical outcome of patients diagnosed with normal or mildly dysfunctional valve is undefined. METHODS AND RESULTS: In 212 asymptomatic community residents from Olmsted County, Minn (age, 32+/-20 years; 65% male), bicuspid aortic valve was diagnosed between 1980 and 1999 with ejection fraction > or =50% and aortic regurgitation or stenosis, absent or mild. Aortic valve degeneration at diagnosis was scored echocardiographically for calcification, thickening, and mobility reduction (0 to 3 each), with scores ranging from 0 to 9. At diagnosis, ejection fraction was 63+/-5% and left ventricular diameter was 48+/-9 mm. Survival 20 years after diagnosis was 90+/-3%, identical to the general population (P=0.72). Twenty years after diagnosis, heart failure, new cardiac symptoms, and cardiovascular medical events occurred in 7+/-2%, 26+/-4%, and 33+/-5%, respectively. Twenty years after diagnosis, aortic valve surgery, ascending aortic surgery, or any cardiovascular surgery was required in 24+/-4%, 5+/-2%, and 27+/-4% at a younger age than the general population (P<0.0001). No aortic dissection occurred. Thus, cardiovascular medical or surgical events occurred in 42+/-5% 20 years after diagnosis. Independent predictors of cardiovascular events were age > or =50 years (risk ratio, 3.0; 95% confidence interval, 1.5 to 5.7; P<0.01) and valve degeneration at diagnosis (risk ratio, 2.4; 95% confidence interval, 1.2 to 4.5; P=0.016; >70% events at 20 years). Baseline ascending aorta > or =40 mm independently predicted surgery for aorta dilatation (risk ratio, 10.8; 95% confidence interval, 1.8 to 77.3; P<0.01). CONCLUSIONS: In the community, asymptomatic patients with bicuspid aortic valve and no or minimal hemodynamic abnormality enjoy excellent long-term survival but incur frequent cardiovascular events, particularly with progressive valve dysfunction. Echocardiographic valve degeneration at diagnosis separates higher-risk patients who require regular assessment from lower-risk patients who require only episodic follow-up.
Keywords: Follow-Up Studies; prospektivní studie; senioři nad 80 let; incidence; analýza přežití; Minnesota; lidé; Humans; prediktivní hodnota testů; následné studie; lidé středního věku; srdeční selhání; Middle Aged; Aged, 80 and over; Predictive Value of Tests; Stroke Volume; longitudinální studie; dopplerovská echokardiografie; Female; Male; Adult; Prospective Studies; Survival Analysis; tepový objem; Longitudinal Studies; mužské pohlaví; Aged; aortální chlopeň; ženské pohlaví; Severity of Illness Index; Aortic Valve Insufficiency; stupeň závažnosti nemoci; Heart Failure; dospělí; aortální insuficience; Incidence; Aortic Valve; Echocardiography, Doppler; senioři